ENDOCRINE PATHOLOGY. ETIOLOGY AND PATHOGENESIS OF ENDOCRINOPATHY: DYSFUNCTION OF THYROID AND PARATHYROIND GLANDS - P. F. Litvitskii ("Paediatrician" Publishers LLC, 2012)
This lecture deals with etiology, pathogenesis and clinical presentation of thyroid and parathyroid hyper - and hypofunction, adrenal pathology. This lecture is also supplemented with multiple choice tests and a clinical case with keys for self testing.